The political economy of trade and migration: Evidence from the US Congress - Paola Conconi; Giovanni Facchini; Max Friedrich Steinhardt; Maurizio Zanardi (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
Over the last decades, the United States has become increasingly integrated in the world economy. Very low trade barriers and comparatively liberal migration policies have made these developments possible. What drove US congressmen to support the recent wave of globalization? While much of the literature has emphasized the differences that exist between the political economy of trade and migration, in this paper we find that important similarities should not be overlooked. In particular, our analysis of congressional voting between 1970 and 2006 suggests that economic drivers that work through the labor market play an important role in shaping representatives' behavior on both types of policies. Representatives from more skilled-labor abundant districts are more likely to support both trade liberalization and a more open stance vis-à-vis unskilled immigration. Still, important systematic differences exist: welfare state considerations and network effects have an impact on the support for immigration liberalization, but not for trade; Democratic lawmakers are systematically more likely to support a more open migration stance than their Republican counterparts, and the opposite is true for trade liberalization.
Keywords: F22; J61; 330; Trade Reforms; Immigration Reforms